170k views
0 votes
If h(x)=(fog)(x) and h(x)=³√x+3, find g(x) if f(x) =³√x+2

User Pieroxy
by
5.0k points

1 Answer

6 votes

Answer:


g(x)=x+1

The problem:

Find
g(x) if
h(x)=(f \circ g)(x),


h(x)=\sqrt[3]{x+3}, and


f(x)=\sqrt[3]{x+2}.

Explanation:


h(x)=(f \circ g)(x)


h(x)=f(g(x))

Replace
x in
f(x)=\sqrt[3]{x+2} with
g(x) since we are asked to find
f(g(x)):


\sqrt[3]{x+3}=\sqrt[3]{g(x)+2}


\sqrt[3]{x+1+2}=\sqrt[3]{g(x)+2}

This implies that
x+1=g(x)

Let's check:


(f \circ g)(x)


f(g(x))


f(x+1)


\sqrt[3]{(x+1)+2}


\sqrt[3]{x+1+2}


\sqrt[3]{x+3} which is the required result for
h(x).

User Arahant
by
5.5k points